Application of models for forecasting of enterprise bankruptcy - Garškaitė, Kristina (Business: Theory and Practice, 2008)
The essence of the models, meant for forecasting of bankruptcy of enterprises, is a complex index, which covers various spheres of the enterprises’ activity and which allows to evaluate the threat of bankruptcy of enterprises according to the fixed critical limits of values. Several models, meant for forecasting of bankruptcy of enterprises, which imply application of the lineal discriminant analysis, were selected, i.e. the Altman method (the first one – the two indices model, the second one – the model for enterprises, the shares of which quote at the securities exchange, the third one – the model for enterprises, the shares of which do not quote at the securities exchange), the Lis, Tafler and Springate methods. The analysis of Lithuanian enterprises, including the operating ones and the ones, which have gone bankrupt after the period under review, was done, seeking to ascertain feasibility of application of the models, meant for forecasting of bankruptcy.Article in Lithuanian.Įmonių bankroto prognozavimo modelių taikymasSantrauka. Įmonių bankroto prognozavimo modelių esmė – kompleksinis rodiklis, apimantis įvairias įmonių veiklos sritis, leidžiantis  įvertinti  įmonių  bankroto  grėsmę  pagal  nustatytas  kritines  reikšmių  ribas.  Pasirinkta  keletas  įmonių  bankroto prognozavimo modelių, kuriuose naudojama tiesinė diskriminantinė analizė: Altmano (pirmasis – dviejų rodiklių modelis; antrasis –įmonių, kurių akcijos kotiruojamos vertybinių popierių biržoje, modelis; trečiasis –įmonių, kurių akcijos nekotiruojamos biržoje, modelis), Liso, Taflerio, Springate. Siekiant išsiaiškinti bankroto prognozavimo modelių taikymo tinkamumą Lietuvos įmonėms, buvo atlikta 20 Lietuvos įmonių, tarp kurių tebeveikiančios ir bankrutavusios po nagrinėjamo laikotarpio įmonės, analizė.Reikšminiai  žodžiai:  įmonių  bankroto  prognozavimas,  bankroto  prognozavimo  modeliai,  bankroto  tikimybė,  finansiniai rodikliai, įmonių veiklos būklė.First published online: 22 Dec 2008